2020
DOI: 10.1016/j.brs.2019.08.004
|View full text |Cite
|
Sign up to set email alerts
|

Transcranial direct current stimulation facilitates response inhibition through dynamic modulation of the fronto-basal ganglia network

Abstract: Background: Response inhibition refers to the ability to stop an on-going action quickly when it is no longer appropriate. Previous studies showed that transcranial direct current stimulation (tDCS) applied with the anode over the right inferior frontal cortex (rIFC), a critical node of the fronto-basal ganglia inhibitory network, improved response inhibition. However, the tDCS effects on brain activity and network connectivity underlying this behavioral improvement are not known.Objective: This study aimed to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
40
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(40 citation statements)
references
References 65 publications
(52 reference statements)
0
40
0
Order By: Relevance
“…However, a later study by Friehs and Frings (2019) did not find a modulation of error rates in any form but only a significant increase in SSRT after cathodal tDCS (c-tDCS). Sandrini et al (2020) further verified that both the rDLPFC and right inferior parietal cortex (rIPC) represent an essential part of the fronto-basal-ganglia network, which is critical for rapid response inhibition. Accordingly, Aron et al (2014) proposed that DLPFC implements task rules rather than inhibition.…”
Section: Introductionmentioning
confidence: 74%
See 1 more Smart Citation
“…However, a later study by Friehs and Frings (2019) did not find a modulation of error rates in any form but only a significant increase in SSRT after cathodal tDCS (c-tDCS). Sandrini et al (2020) further verified that both the rDLPFC and right inferior parietal cortex (rIPC) represent an essential part of the fronto-basal-ganglia network, which is critical for rapid response inhibition. Accordingly, Aron et al (2014) proposed that DLPFC implements task rules rather than inhibition.…”
Section: Introductionmentioning
confidence: 74%
“…Besides IFG, the right dorsolateral prefrontal cortex (rDLPFC) may be engaged in active inhibitory processing of both motor and higher level memory representations (Penolazzi et al 2014;Frings 2018, 2019;Sandrini et al 2020). Using tDCS, Penolazzi et al (2014) reported that cathodal stimulation over rDLPFC leads to decreased inhibition during the standard retrieval-practice paradigm (RPP).…”
Section: Introductionmentioning
confidence: 99%
“…However, these types of distant bipolar montages can result in widespread and diffuse neuromodulation 33,45,46 . In fact, a recent study showed that anodal IFG stimulation not only altered the functional connectivity and neural activity in the fronto-basal-ganglia network presumed to implement response inhibition, but that it also induced activity changes in both the dorsolateral prefrontal and the inferior parietal cortices 47 . Such widespread modulations raise the possibility that other regions might drive the previously reported effects.…”
Section: Discussionmentioning
confidence: 99%
“…6 While CRPs may promote the development of an automatic association between a specific cue and a No-go response 7 by enhancing frontal top-down inhibitory control, 8 active tDCS over the right inferior frontal cortex (rIFC) or the right dorsolateral prefrontal cortex (rDLPFC) is thought to induce specific neural modifications including the fronto-basal-ganglia network. 9,10 In a recent meta-analysis, Khaleghi et al 11 highlight that unilateral tDCS over DLPFC leads to less risk-taking behaviors in healthy individuals through the neuromodulation of the meso-cortico-limbic dopamine system. Combining training with tDCS is nowadays thought to improve training outcomes through synergistic effects, as tDCS may enhance the training effect by facilitating learning through specific neuroplastic changes, while training could magnify the acute effect of the neuroplasticity intervention.…”
Section: Introductionmentioning
confidence: 99%